Carta ao Leitor - Reali, Aline Maria de Medeiros Rodrigues (Revista Eletrônica de Educação, 2015)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> DOI: http://dx.doi.org/10.14244/198271991457 Carta ao leitor v. 9, n.3, 2015.